The tropical highland blackberry (Rubus adenotrichos Schltdl.) as a potential functional food: a look at the research carried out - Schmidt-Durán, Alexander (2024)
Blackberry (Rubus adenotrichos Schltdl.) has been classified as a fruit with high potential as a functional food, due to its high concentration of ellagitannins and anthocyanins. Therefore, the aim of this study is to compile the research articles performed with these species, from agronomical to tissue culture studies, to analysis of fruit compounds and fruit juice processing; and the potential health benefits from this fruit in studies performed in vitro and in vivo, as well as the possibility of using  biotechnological tools for bioprocessing and upscaling the production of compounds of interest, compiling, in the same units of measure, the concentration of the main bioactive blackberry compounds.